Trends in antimicrobial resistance in Malaysia - Mohamed Naeemmudeen, Nashreeyn; Mohd Ghazali, Nur Ainaa Nabihah; Bahari, Hasnah; Ibrahim, Rosni; Samsudin, Ahmad Dzulfikar; Jasni, Azmiza Syawani (Malaysian Medical Association, 2021)
Introduction: Antibiotic resistance is a burgeoning problem worldwide. The trend of bacterial resistance has increased over the past decade in which more common bacteria are becoming resistant to almost all the antibiotics currently in use, posing a threat to humans and even livestock. Methods: The databases used to search for the relevant articles for this review include PubMed, Science Direct, and Scopus. The following keywords were used in the search: Antimicrobial resistance, Malaysian action plan, antibioticresistant bacteria, and Malaysian National Surveillance on Antimicrobial Resistance (NSAR). The relevant articles published in English were considered. Results: The antibiotic-resistant bacteria highlighted in this review showed an increase in resistance patterns to the majority of the antibiotics tested. The Malaysian government has come up with an action plan to create public awareness and to educate them regarding the health implications of antibiotic resistance. Conclusion: Antimicrobial resistance in Malaysia continues to escalate and is attributed to the overuse and misuse of antibiotics in various fields. As this crisis impacts the health of both humans and animals, therefore a joined continuous effort from all sectors is warranted to reduce the spread and minimize its development.